2014
DOI: 10.1186/s40200-014-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic peripheral neuropathy in Iran: a systematic review and meta-analysis

Abstract: Diabetic peripheral neuropathy (DPN) is an important microvascular complication of diabetes mellitus (DM). It is a major contributor to foot ulceration and lower limb amputation in persons with DM and have also a significant negative effect on patient's quality of life. This meta-analysis reviews prevalence of DPN among patients with type 1 and 2 DM in Iran. Using PubMed and NLM Gateway (for MEDLINE), Institute of Scientific Information (ISI), and SCOPUS as the main international electronic data sources, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 17 publications
4
45
3
2
Order By: Relevance
“…17 Sobhani S et al study suggests that the prevalence of neuropathy is very high among the population with diabetes in Iran but they have not given any percentage of prevalence whereas our current study revealed 60% of prevalence of neuropathy in the diabetic patients. 18 Mythili A et al …”
Section: Discussionmentioning
confidence: 99%
“…17 Sobhani S et al study suggests that the prevalence of neuropathy is very high among the population with diabetes in Iran but they have not given any percentage of prevalence whereas our current study revealed 60% of prevalence of neuropathy in the diabetic patients. 18 Mythili A et al …”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to different types of diabetes, existing health care facilities, sample selection, different diagnostic criteria used, variable methods etc. [6–8]. …”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimated that the prevalence of diabetes would be equal to 171 million people in 2000 and it would reach to 438 million people by 2030 (Sobhani et al, 2014). Most of this increase is taking place in developing countries, and as estimated, about 75% of diabetics will live in these countries by 2025 (Saeidpour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A person died of diabetes at every 10 seconds (Shahab Jahanlu et al, 2015). Due to the direct association of this disease with increased prevalence of cardiovascular, cerebrovascular, peripheral arteries, retinopathy, neuropathy, nephropathy, diabetic foot, amputation and depression diseases (Sobhani et al, 2014), it has a direct impact on the health care costs, and also increases the mortality in people (Kermansaravi et al, 2011), so that the average age of life expectancy in diabetics reduces to 15 years, and it finally has a negative impact on their quality of life (Lioyd et al, 2011). Quality of life refers to the individuals' satisfaction with some life fields which are important to them (Lioyd & Orchard, 1999).…”
Section: Introductionmentioning
confidence: 99%